Loyalty vs deception: the truth behind 'organic' and 'free-range' brand labels - Hughes, Sarah-Jane (The IIE, 2016)
The purpose of this research study is to investigate how brand labels can affect and change consumer’s perceptions and expectations surrounding ‘organic’ and ‘free-range’ produce, versus the truth. The importance of this research is to give consumers access to the necessary information needed in order to make informed decisions about the foods they are choosing to consume. Brands need to educate consumers about organic and free-range produce to ensure they make informed decisions. There is a background of knowledge around the topic, and research is constantly being developed and studied. The research needs to come from a feasible source, and needs to be done in a way that ensures consumers are not being manipulated and taken advantage of. This will be used to help educate consumers and give them access to the necessary information required. Relevant data for this study is analysing the organic and free-range market and systems that are in place within South Africa. As well as consumer’s perceptions and expectations of this produce, and how labels affect consumers purchasing power. Health conscious consumers between the ages of 21-49 years. The research study will find: That there is a need for a nation wide logo or stamp that ensures the product is free-range or organic. Consumers aren't aware that brands label products as organic and free range based a narrow set of guidelines and legislation's. Consumers want more knowledge and information about organic and free range produce. Through three focus groups containing 10 individuals in each,15 of these individuals were women and 15 men. These individuals had to shop at Woolworths and purchase organic and free-range produce. Individuals were asked the same set of questions and created a discussion around these several questions. The study recorded notes during the focus groups and used this information to gain core insights about the study. Through these core insights the study will be able to compile a solution to address these areas. The solutions will address concern areas and make feasible and legitimate solutions. The study will create awareness about what brands and the industry needs to do. This study will contribute to the agricultural sector and help brands by educating them on what their consumers want to know about their produce. This study will provide information about what consumers want to know about their produce and who they want to gain the information from. Both brands and the industry can implement the solutions to ensure its success. "LOYALTY VS DECEPTION”
Thesis
Keywords: Brand labels; Consumer's perceptions; Organic; Free- range; Loyalty vs Deception